Effects of early enteral nutrition on T helper lymphocytes of surgical septic patients: A retrospective observational study. Issue 32 (August 2017) - Sun, Jia-Kui; Yuan, Shou-Tao; Mu, Xin-Wei; Zhang, Wen-Hao; Liu, Ying; Zou, Lei; Wang, Xiang; Zheng, Shu-Yun
Abstract : Abstract: The aim of this study was to investigate the effects of early enteral nutrition (EEN) on T helper lymphocytes and the subpopulations ratios of surgical septic patients. We performed a retrospective study including 107 eligible patients from February 2014 to December 2015. Patients were divided into EEN, delayed enteral nutrition (DEN), or total parenteral nutrition (TPN) group according to the duration before enteral feeding. Th1, Th2, Th17, and Treg lymphocyte percentages were collected on days 3, 7, and 14 after admission. The disease severity and clinical outcome variables were also recorded. The Th1, Th17 percentages, and Th1/Th2, Th17/Treg ratios of EEN group were significantly lower than those of DEN or TPN group on the 14th day after admission ( P < .05). Compared with TPN, DEN might have a tendency to decrease the Th1 and Th17 percentages. EEN could improve the disease severity and clinical outcomes of septic patients, however, no difference on 28-day mortality was found between EEN and DEN group. EEN could improve the dysregulation of Th1/Th2 and Th17/Treg ratios during early stage of sepsis. Compared with DEN, EEN could improve the disease severity and clinical outcomes, but not decrease the 28-day mortality of surgical septic patients.